2007
DOI: 10.4103/1817-1737.32230
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of multidrug-resistant organisms causing ventilator-associated pneumonia in a tertiary care hospital: A nine months′ prospective study

Abstract: BACKGROUND:Ventilator-associated pneumonia (VAP) is an important intensive care unit (ICU) infection in mechanically ventilated patients. VAP occurs approximately in 9-27% of all intubated patients. Due to the increasing incidence of multidrug-resistant organisms in ICUs, early and correct diagnosis of VAP is an urgent challenge for an optimal antibiotic treatment.AIM OF THE STUDY:The aim of the study was to assess the incidence of VAP caused by multidrug-resistant organisms in the multidisciplinary intensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
20
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 29 publications
7
20
1
Order By: Relevance
“…was the commonest isolate (37.83%) followed by P. aeruginosa (24.32%) in both early and late onset VAP. Similar findings were reported by Dey et al, (2007).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…was the commonest isolate (37.83%) followed by P. aeruginosa (24.32%) in both early and late onset VAP. Similar findings were reported by Dey et al, (2007).…”
Section: Resultssupporting
confidence: 82%
“…Enterobacteriaceae isolated showed a high level of resistance to betalactam antibiotics and were sensitive to carbapenems. Such a high level of drug resistance has also been documented in studies conducted by Joseph et al, (2009) and Dey et al, (2007).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…In our study the rate of carbapenemase-producing bacteria among all GNB was 48% which is higher than other studies published in recent past,[22] vast majority of these carbapenemase 19/24 (79.16%) were also from Enterobacteriaceae family. Various other studies have from India have shown a rate between 18.75 and 26%.…”
Section: Discussioncontrasting
confidence: 67%
“…from the same hospital. In the study of Dey and Bairy, 30 MBL was reported only in 21.7% of Acinetobacter spp. The coexistence of multiple MBL genes in bacteria is an alarming situation.…”
Section: Discussionmentioning
confidence: 89%